Acute Myocarditis Mimicking an Acute Coronary Syndrome: Case Report and Mini-Review of the Literature - Fatima Ezzahraa Talhi; Monia Elmourid; Anass Maaroufi; Zakaria Qechchar; Salim Arous; El Ghali Bennouna; Leila Azzouzi; Rachida Habbal (International Journal of Cardiovascular Practice, 2019)
Acute myocarditis is often a challenging diagnosis due to a lack of specific clinical or paraclinical signs. It can be presented by a severe chest pain and localized ST elevation on Electrocardiogram, in rare cases, misleading the diagnosis towards acute coronary syndrome. After routine coronary angiography, a cardiac magnetic resonance imaging is imposed to correct the diagnosis towards acute myocarditis. We report the observation of a 19 year-old Moroccan male admitted to the cardiology department of IBN ROCHD University hospital of Casablanca, for acute myocarditis misdiagnosed initially as an acute myocardial infarction ST elevation and confirmed by cardiac magnetic resonance imaging.